Physical optimization of thermostable alkaline protease by E. coli BL21 (DE3) plyss harboring 50a protease gene using response surface methodology - Nor Hidayah Bohari; Noor Azlina Ibrahim (2016)
Physical optimization is important for enzyme production by fermentation process. In general, fermentation process at optimal condition increases the expression and production level of enzyme to many times in comparison with their natural production. This study was focused on the optimization of the physical factors that influenced the thermostable alkaline protease production. The induction and incubation time were studied using conventional method while the other three factors which are incubation temperature, initial pH of medium and agitation speed were optimized by response surface methodology (RSM). The interaction effects among these factors were explained using response plot and the model adequacy was satisfactory as the coefficient of determination (R²) was 96.48%. The enhancement of thermostable protease from 197.83 U/ml to 325.89 U/ml was achieved using both conventional and statistical approach of response surface methodology (RSM). This present study proved that physical optimization significantly affects the protease production and the optimum physical condition obtained may applied in large scale process.